From NAFTA to USMCA: Two’s Company, Three’s a Crowd - Condon, Bradly J. (Latin American Journal of Trade Policy, 2019)
The renegotiation of NAFTA was surrounded by a dramatic atmosphere, just as Canadian Minister of Foreign Affairs Chrystia Freeland predicted. The negotiations took place against a backdrop of unilateral trade measures, President Trump’s mercantilist approach to trade policy, and the United States’ specified preference for bilateral trade deals. This article argues that, for the most part, economic, political and cultural relations in the NAFTA countries are bilateral in nature, but with important trilateral production chains in specific sectors, most notably in the automotive sector. Beyond these trilateral sectors, the relationship between Canada and Mexico plays a relatively minor role. However, replacing NAFTA with bilateral agreements would have placed Canada and Mexico at a disadvantage, relative to the United States, in terms of attracting foreign direct investment. Nevertheless, Canadian and Mexican interests do not always coincide, nor do their negotiating positions. For example, Mexico was willing to give up Chapter 19 dispute settlement for trade remedies, whereas Canada insisted on keeping it in place. In end, USMCA Chapter 10 preserves this dispute settlement mechanism for all three parties. Canada was willing to give up NAFTA Chapter 11 on foreign investment disputes, whereas Mexico accepted a modified version. The result is a trilateral agreement with significant bilateral elements, as well as global elements that will serve as a possible model in future megaregional and multilateral negotiations.